Minimally invasive techniques in bariatric surgery: A literature review (Research, Society and Development, 2024)
Introduction: Bariatric surgery represents an effective approach in combating morbid obesity and its respective comorbidities. It is noted that minimally invasive procedures, such as laparoscopy and robotic surgery, have stood out for presenting lower complication rates, faster recovery, and shorter hospital stays compared to traditional surgeries. Objectives: This article aims to review the advantages and challenges of minimally invasive procedures in bariatric surgery, focusing on aspects such as complication rates, recovery, hospital stay duration, and the challenges in implementing these techniques, including costs and resistance to adopting new technologies. Results: The analysis indicated that minimally invasive techniques offer substantial clinical benefits, including lower complication rates and faster recovery, which translates into significant economic advantages by reducing hospital costs. However, the implementation of these techniques faces notable obstacles, such as the high cost of equipment and the need for specialized training for healthcare professionals. Conclusion: The adoption of minimally invasive techniques, such as laparoscopy and robotic surgery, is essential to improve clinical and economic outcomes in bariatric surgery. Despite challenges such as costs and technological resistance, the efficacy and safety of these approaches highlight the need for their broader incorporation. Continued research and the adoption of evidence-based practices are fundamental to optimizing the treatment and prevention of morbid obesity.